Composição nutricional, perdas e estabilidade aeróbica de silagens de milho submetidas à diferentes períodos de estocagem - Pereira, Stela Naetzold (2019)
This study aimed to evaluate the effects on nutritional quality, fermentation, kinetic parameters, losses inherent to the aerobic and anaerobic processes and the protein fractions and glicídicas of silages open at different times of storage 45, 90, 180 and 360 days after the opening remained exposed to the environment with controlled temperature of 25 ºC during 96 hours to evaluate the composition and stability. The estimates of temperature, pH, N-NH3 and MS were performed once a day and the nutritional assessment of the silages was performed at the opening and after 96 hours of exposure to the air. The experimental design was a completely randomized block design, with four treatments and four replicates each. The nutritional composition of the silage was changed by the time of storage as well as by exposure to air, since there was an increase in the fractions NDF, ADF, Lda and the production of effluent, causing a reduction of soluble fractions of carbohydrates, while the MS, ash, losses and the RMS were not affected by storage time and exposure. The concentration of lactic acid, acetic acid and the pH showed a quadratic effect with higher levels with 233, 162 and 264 days, reducing later, while the propionic acid increased progressively with the time of storage. In relation to the N-ammoniacal nitrogen concentration was observed increased with storage time and reducing the exposure time of silage to air. We also observed that the time of storage has changed the composition of the silages, fertilization with the increase of the NS, NNP and the reduction of true protein, while the NIDA was not affected by treatments. For the kinetic parameters of degradation of the silages observed quadratic effects for the production of gas with higher levels to 310 days and the fraction presented decrease and its degradation rate of B increased throughout the storage time. The other parameters were not affected (P>0.05). The starch content and the digetibilidade of MS showed quadratic effects and the TDN increased, while the estimate of milk production, net energy for lactation, and digestibility of NDF was not affected by storage time. The temperatures of the silages increased regardless of the time of storage and exposure to air in which they were. The stability loss occurred before the 24 hours of exposure to air, at all times of storage evaluated. To the extent that increases the storage time, we observed a reduction in quality of silages, due to the increase in the production of effluent, the levels of N-ammoniacal nitrogen, the NNP, the cell wall and the loss of true protein and soluble carbohydrates. The time of exposure of the silage to the environment should be reduced to the maximum, since the pH and temperature increased with the passing of the hours of exposure, causing greater aerobic deterioration of the silage material.